The legal implications of the WIPO treaty on intellectual property, genetic resources and associated traditional knowledge on indigenous peoples of Uganda and Kenya - Basimanyane, Dorcas K. (University of Pretoria, 2025)
Mini Dissertation (LLM (International Trade and Investment law in Africa))--University of Pretoria, 2025.